On Global Attractors for a Class of Parabolic Problems - Figueroa-Lopez, Rodiak [UNESP]; Lozada-Cruz, German [UNESP] (Natural Sciences Publishing Corp-nsp, 2014)
This paper is devoted to study the existence of global attractor in H-0(1)(Omega) and uniform bounds of it in L-infinity(Omega) for a class of parabolic problems with homogeneous boundary conditions wich involves a uniform strongly elliptic operator of second order in the domain Omega subset of R-n. The main tools used to prove the existence of global attractor are the techniques used in Hale [8] and Cholewa [5], and for the uniform bound of the attractor we use the Alikakos-Moser iteration procedure [1].
Keywords: Parabolic equation; sectorial operator; global attractor; uniform boundness